Flipped English Learning Readiness of Rural College EFL Students: A Survey Study - Mudra, Heri (Universitas Terbuka, 2024)
Lately, internalization of online learning into physical meeting during English learning has become a trend. This study aimed to describe perceptions of rural-college EFL students regarding flipped English learning readiness. A total of 217 EFL students participated in this survey study. The results showed that several EFL students prefer watching online videos than reading and summarizing reading materials. Online discussion appears to be more practical and efficient compared to physical mode. However, the EFL students expect more on college teacher support during online or physical meetings. In short, flipped learning readiness, for rural-college EFL students, enhances enthusiasm to study English. Moreover, different levels of readiness indicates that there should be continuous improvement towards supporting aspects, including policy, tools, curriculum, process, and teaching and learning strategies.